Development and Implementation of Greater Learning Model Integrated Structured Tasks to Improve Student's Concepts Understanding - Nurul Aulia Rahman; Sudir Umar; Topan Setiawan (EduLine: Journal of Education and Learning Innovation, 2022)
This study was conducted at the Chemistry Education Study Program, Faculty of Teacher Training and Education, Khairun University. This study aims to develop the GREATER-2T learning tool and its implementation to students' understanding of concepts in basic chemistry 1 course & teaching and learning strategies of chemistry. The population and sample in this study were all students of the chemistry education study program who programmed chemistry teaching and learning planning courses and chemical research methodology, the odd semester of the 2021/2022 academic year. Sample selection using saturated sampling technique. The method used in this research is research and development ( research and development ). The products to be developed are learning tools in the form of lecture program units (SAP), learning implementation plans (RPP), and teaching materials. The development model used by Plomp consists of 5 stages, namely: 1) initial investigation, (2) design, (3) realization/construction, (4) evaluation and revision, and (5) implementation. The research instruments were in the form of validation sheets for learning tools and teaching materials, student response assessment sheets, and concept mastery assessment instruments. Data analysis used descriptive and inferential analysis, using the SPSS software.